Behaviour of zinc complexes and zinc sulphide nanoparticles revealed by using screen printed electrodes and spectrometry - Nejdl, Lukas; Ruttkay-Nedecky, Branislav; Kudr, Jiří; Kremplova, Monika; Cernei, Natalia; Prasek, Jan; Konecna, Marie; Hubalek, Jaromir; Zitka, Ondrej; Kynicky, Jindrich; Kopel, Pavel; Kizek, Rene; et al. (Sensors (Basel, Switzerland), 2013)
In this study, we focused on microfluidic electrochemical analysis of zinc complexes (Zn(phen)(his)Cl2, Zn(his)Cl2) and ZnS quantum dots (QDs) using printed electrodes. This method was chosen due to the simple (easy to use) instrumentation and variable setting of flows. Reduction signals of zinc under the strictly defined and controlled conditions (pH, temperature, flow rate, accumulation time and applied potential) were studied. We showed that the increasing concentration of the complexes (Zn(phen)(his)Cl2, Zn(his)Cl2) led to a decrease in the electrochemical signal and a significant shift of the potential to more positive values. The most likely explanation of this result is that zinc is strongly bound in the complex and its distribution on the electrode is very limited. Changing the pH from 3.5 to 5.5 resulted in a significant intensification of the Zn(II) reduction signal. The complexes were also characterized by UV/VIS spectrophotometry, chromatography, and ESI-QTOF mass spectrometry.